Ratios in Agriculture: A Rice Fertilization Context for Ratio Learning Trajectory - Sari, Filian Yunita; Putri, Ratu Ilma Indra; Susanti, Ely; Zulkardi (Mathematics Education Journal, 2025)
This study aims to develop a learning trajectory for ratio material using rice fertilization context. This study employed validation studies within a design research framework involving seventh-grade students at a junior high school in Belitang. Data was collected through student activity sheets, observations, and interviews. Design research consists of three stages: experimental preparation, experimental design, and retrospective analysis. The findings indicate that the learning trajectory for ratio material in the rice fertilization context includes identifying patterns and relationships between two quantities, determining the simplest unit ratios, representing ratios using ratios table, and solving real-world ratio-related problems. These results confirm that the designed learning trajectory serves as a practical reference for teachers in designing ratio learning that is meaningful, applicable, and relevant to the life experiences of students in agricultural areas, while supporting sustainable agriculture.